Multilevel Analysis: Factors Associated with Overweight and Obesity in Primary School Children in Surakarta, Central Java - Arum Kusuma Rini; Eti Poncorini Pamungkasari; Bhisma Murti (Journal of Epidemiology and Public Health, 2019)
Background: Life course studies have shown that early onset obesity is a risk factor for morbidity and mortality later in life. In both sexes, rates of diabetes, coronary heart disease, atherosclerosis, hip fracture, and gout were increased in those who were overweight as adolescents. Contextual factor at higher level such as school may have indirect effect on the incidence of overweight or obesity through eating behavior. However, studies into factors affecting child obesity in Indonesia using multilevel approach are lacking. This study aimed to examine factors associated with overweight and obesity in primary school children in Surakarta, Central Java, using multilevel analysis.Subjects and Method: A case control study was conducted at 25 primary schools in Surakarta, Central Java, from March to April 2018. A sample of 225 primary school children was selected by fixed disease sampling, consisting of 75 children with overweight or obesity and 150 children with normal weight. The variables of children were placed at the first level of the multilevel model. The potential contextual effect of school was determined at the second level. The dependent variable was overweight or obesity. The independent variables were maternal education, maternal body mass index (BMI), physical activity, family income, and school environment. The data were collected by questionnaire and analyzed by a multilevel logistic regression run on Stata 13.Results: Child overweight or obesity was positively associated with maternal BMI ?25 (b= 0.11; 95% CI= 0.04 to 0.18; p= 0.002) and high family income (b= 0.04; 95% CI= 0.02 to 0.06; p< 0.001). Child overweight or obesity was negatively associated with high physical activity (b= -0.03; 95% CI= -0.05 to -0.01; p= 0.009). School environment had a negligible contextual effect on child obesity with ICC= 5.08%.Conclusion: Child obesity is positively associated with maternal BMI ?25 and family income, and is negatively associated with physical activity. School environment has a negligible contextual effect on child obesity.Keywords: obesity, primary school children, maternal body mass index, physical activityCorrespondence: